Undang-Undang Desa: Sebuah Kontribusi terhadap Literatur dan Kebijakan - Setiadi, Deddy; Zeinuddin, Moh.; Munir, Miftahul (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
The main focus of this research is on the understanding, implementation, and impact of the Village Law on financial governance at the village level. This research is expected to contribute to the literature on village financial governance, assist stakeholders in designing more effective policies, and encourage further research to optimize the village financial management system in accordance with the times. The normative juridical research method involves literature study and document analysis to understand the legal provisions contained in the relevant laws. The research identifies key principles in the law that impact on village financial management, including budget allocation, financial reporting, and accountability. Through a contemporary review, the research also evaluates the extent to which the laws reflect the dynamics of social, economic, and policy changes in village communities. The results provide an in-depth understanding of the implementation of relevant laws and the challenges faced by village governments in managing their finances. The findings provide a foundation for critical thinking regarding sustainability and improvement in the village financial management system, as well as for policy development that is more responsive to village needs and dynamics.